ユウヒョウ キ ノ ナンキョク カイ ヒョウジョウ ノ アイスホール デ カンソク サレタ エンブン セイソウ ノ ビサイ コウゾウ - 松田, 治; マツダ, オサム; 石川, 慎吾; イシカワ, シンゴ; 川口, 弘一; カワグチ, コウイチ; Matsuda, Osamu; Ishikawa, Shingo; Kawaguchi, Kouichi (1990)
P(論文) 第25次南極地域観測隊の海洋生物環境調査の一環として, 昭和基地付近の定着氷上の1定点(観測用アイスホール)において海水温度と塩分の季節変化を1984年3月より1985年1月まで観測した。その結果, 夏季の上層海水中に水温・塩分の成層状態が認められた。この融氷期におけるアイスホール内の水温・塩分成層の微細構造を明らかにするため1985年1月に深度層5-10cm間隔の精密観測を実施したところ, 海面下120cmから150cm間に, 塩分が3.33から27.88‰まで変化する顕著な塩分躍層が観測された。この塩分躍層は海氷直下とほぼ同水準に位置したのでアイスホール周辺の海氷直下は著しい低塩分にさらされていると推定された。このような状況は融氷期の底なしパドルやクラックの周辺にも存在すると考えられ, そこでは海氷下面のアイス・アルジーが低塩分環境により生理学的な影響を受けているものと推定された。 Observation on the seasonal variation of temperature and salinity of seawater was carried out through an ice hole at a station near Syowa Station as part of the 25th Japanese Antarctic Research Expedition. During the period from March 1984 to January 1985,temperature salinity stratification was observed only in summer in the upper layers of the seawater. In order to clarify the microstructure of the stratification, fine-scale observations on temperature and salinity profiles were conducted through the ice hole with the use of the CSTD monitor at the depth intervals from 5 to 10 cm on January 6,1985. The results revealed that an intensified halocline occurred at the depth between 120 and 150 cm, where salinity changed considerably from 3.33 to 27.88‰. This observed halocline is supposed to exist in the underlying seawater immediately below sea ice around the ice hole. Such a condition may naturally occur in the area of paddles with thawing holes and cracks. Ice algae inhabiting the undersurface of ice may be physiologically affected by the extremely low salinity of the underlying seawater. departmental bulletin paper